Dialéctica y gramática en el estoicismo antiguo (Argos, 2025)
This paper deals with the theorical phaenomena which put the Stoic dialectic as main point of the constitution of Grammar through the fundamental division in a branch of dialectic dealing with what is signified, and another with what has signifícation. Then, it proposes a critical study regarding the status of the tradicional polemic 'analogists vs. anomalists' that shows plainly the relationship between Stoic dialectic and Alexandrian philology, and the common basis that made possible the connections between them. This way reveals that technical grammar did not separate itself from its Stoic theorical origin and that the influence of both branches of dialectic is present in its mature stages.
Keywords: dialectic; grammar; analogy; anomaly; Stoicism